The Anglo-Norman historical canon : publishing and manuscript culture - Tahkokallio, Jaakko (Cambridge University Press, 2019)
This Element is a contribution to the ongoing debate on what it meant to publish a book in manuscript. It offers case-studies of three twelfth-century Anglo-Norman historians: William of Malmesbury, Henry of Huntingdon, and Geoffrey of Monmouth. It argues that the contemporary success and rapid attainment of canonical authority for their histories was in significant measure the result of successfully conducted publishing activities. These activities are analysed using the concept of a 'publishing circle'. This concept, it is suggested, may have wider utility in the study of authorial publishing in a manuscript culture. This Element is also available as Open Access.
Title from publisher's bibliographic system (viewed on 10 Jun 2019).
Keywords: Book industries and trade -- Great Britain -- History; Historiography -- Great Britain -- History -- To 1500.; William, -- of Malmesbury, -- approximately 1090-1143.; Henry, -- of Huntingdon, -- 1084?-1155.; Geoffrey, -- of Monmouth, Bishop of St. Asaph, -- 1100?-1154.